Public service modernization and trade union reform: towards managerial led renewal? - Bach, Stephen; Givan, Rebecca Kolins (2008)
It is a curious feature of the debate about the UK Labour government's modernization agenda that the consequences for trade unions have been almost wholly neglected. focusing on a case study of UNISON, the public service trade union that is dominant in local government and health, this paper argues that UNISON has emulated key aspects of the modernization agenda, adopting a dual strategy to union renewal. It has attempted to rebuild workplace organization, but has placed strong emphasis on managerial-led renewal, adopting many components of the target culture. These measures have created tensions within the organization that mirror some of the broader contradictions of the modernization agenda. The paper concludes by considering the implications of these findings for public service union renewal. - Reproduced.
Keywords: Trade unions; Administrative reform